2011
DOI: 10.1111/j.1600-9657.2010.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency dental injuries presented at the Beijing Stomatological Hospital in China

Abstract: TDI in Beijing, China not only shows epidemiologic characteristics in common with many other studies in the world, but also shows different characteristics that should be further studied and taken into consideration when planning for preventive programs and emergency resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 15 publications
3
24
1
2
Order By: Relevance
“…They are the most common type of TDIs in the permanent dentition (8). Among all crown fractures, the prevalence of enamel-dentin fractures ranges from 2.5% to 32.6% (14,18,41,(79)(80)(81)87) in the primary dentition and from 2.4% to 33% in the permanent dentition (5,(87)(88)(89)(90).…”
Section: Enamel Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…They are the most common type of TDIs in the permanent dentition (8). Among all crown fractures, the prevalence of enamel-dentin fractures ranges from 2.5% to 32.6% (14,18,41,(79)(80)(81)87) in the primary dentition and from 2.4% to 33% in the permanent dentition (5,(87)(88)(89)(90).…”
Section: Enamel Fracturementioning
confidence: 99%
“…Depending on the pulp involvement, this injury is classified into two categories, that is, uncomplicated and complicated. Crown-root fractures are the least observed crown-related injury with a prevalence ranging from 2% to 2.5% (87,174) in primary teeth and 0.5% to 5% in permanent teeth (174,175) among all TDIs. Little information is available with regard to pulp prognosis in crown-root factures.…”
Section: Crown-root Fracturesmentioning
confidence: 99%
“…It is thus of great importance to evaluate the distribution of pediatric TDIs in China. Despite its importance, few studies have been published regarding this issue in China (10,11). It is therefore necessary to gradually collect related data that could be used to determine global TDI epidemiology.…”
mentioning
confidence: 99%
“…It is well documented that hospital emergency departments (ED) are confronted with triaging and managing dental emergencies of both traumatic and non‐traumatic in origin. In fact, it has been reported that up to 66% of all ED visits for dental issues are for the management of traumatic dental injuries (TDI) .…”
mentioning
confidence: 99%